Analysis of pointing accuracy on petanque standing position: Performance and accuracy - Irawan, Fajar Awang; Ghassani, Dina Syarafina; Permana, Dhias Fajar Widya; Kusumawardhana, Buyung; Saputro, Hananto Tyas; Fajaruddin, Syarief; Bawang, Rex John G (Journal Sport Area, 2022)
In developing the game of pétanque, it is necessary to master good basic techniques because this is the initial capital of an athlete to develop his game. Good mastery of basic techniques can also improve performance optimally. The purpose of this study was to analyze the accuracy of petanque pointing in a standing position at Atlas City Petanque Club (ACPC) athletes in Semarang City. The type of this study is descriptive-quantitative. The sample of this study was 8 athletes of ACPC club in Semarang city consisting one female and seven male athletes. Inclusion criteria in this study was having experience at national or international levels competitions and having trained for at least 6 months. All sample also sign the inform consent as a agreement to participate the research until the end. The results of this study indicate that the analysis of the pointing accuracy in standing position by ACPC club athletes in Semarang City is in the Precise Category, with an average distance of the ball to a target was 0.14 meters. Pointing in a standing position is very effective for a distance of 9 meters due to the ideal body position with a long throw distance from the target. The limitation of this study only focuses on the throwing distance produced by each athlete, so it has not been able to analyze every value generated from each athlete’s throws. Further, research can analyze the backspin technique of pointing in a standing position to complement the current research data.